STRATEGI PEMASARAN PRODUK TABUNGAN HIJRAH HAJI PADA BANK MUAMALAT INDONESIA KANTOR CABANG KOTA PONTIANAK - Azhara, Maulidia Dara (Cross-Border Journal of Business Management, 2024)
This research utilizes a qualitative approach with a descriptive character. The type of research used by the researcher is Field Research. The data used consist of primary data obtained directly in the field in the form of information from related parties, while secondary data is obtained from books and the internet. Data collection techniques include observation, interviews, and documentation. The findings of this research indicate that the strategy employed by BMI is marketing mix or 4P. Product-wise, it involves introducing the Tabungan Hijrah Haji product to the public through religious lectures, socialization in schools, offices, and companies. Price-wise, the Bank Muamalat Indonesia Branch Office in Pontianak offers a reasonably affordable price with a minimum initial deposit of Rp. 100,000,- and subsequent deposits of at least Rp. 50,000,-. This savings account has no administrative fees, minimum balance requirements, and is purely entrusted. In terms of Place, the Bank Muamalat Indonesia Branch Office in Pontianak is strategically located in the city center and close to markets, schools, hospitals, offices, and other facilities. Promotion-wise, it includes advertising on websites and social media, personal selling, publicity through sponsors and donors, direct marketing, and promotional draws. Supporting factors include the length of the waiting list, as the longer the wait for Hajj registration, the more it encourages Muslims to plan their pilgrimage early by opening a Tabungan Hijrah Haji account, as well as the high Muslim population in Pontianak City. On the other hand, inhibiting factors include competition from both Sharia and conventional banks, lack of human resources for operations, and the COVID-19 pandemic in Indonesia.